Stigma, depression, and quality of life among people with pulmonary tuberculosis diagnosed through active and passive case finding in Nepal: a prospective cohort study - Kritika Dixit; Bhola Rai; Tara Prasad Aryal; Noemia Teixeira de Siqueira-Filha; Raghu Dhital; Manoj Kumar Sah; Ram Narayan Pandit; Govinda Majhi; Puskar Raj Paudel; Jens W. Levy; Job van Rest; Suman Chandra Gurung; et al. (BMC, 2024)
Abstract Background The psychosocial consequences of tuberculosis (TB) are key barriers to ending TB globally. We evaluated and compared stigma, depression, and quality of life (QoL) among people with TB diagnosed through active (ACF) and passive (PCF) case-finding in Nepal. Methods We prospectively recruited adults with TB diagnosed through ACF and PCF in four districts of Nepal between August 2018 and April 2019. Participants were interviewed at 8-12 weeks (baseline) and 22-26 weeks (follow-up) following treatment initiation. TB stigma was measured using an adapted Van Rie Stigma Scale (0 = no stigma to 30 = highest stigma). Depression was measured using a locally-validated Patient Health Questionnaire (PHQ-9). Mild and major depression were indicated by  PHQ-9 scores 5-9 and ≥ 10, respectively. QoL was measured using the EuroQoL 5-Dimension 5-level (EQ-5D-5L) from 0 to 1 (optimal QoL); and self-rated health from 0 to 100 (optimal self-rated health). Results We recruited 221 participants (111 ACF; 110 PCF) with a mean age of 48 years (standard deviation [SD] =  ± 16), of whom 147/221 (67%) were men. The mean TB stigma score was 12 (SD = 7.3) at baseline and 12 (SD = 6.7) at follow-up. The most commonly perceived elements of TB stigma at baseline were that people with TB experienced guilt (110/221, 50%) and feared disclosure outside their household (114/221, 52%). Self-rated health and EQ-5D-5L scores increased from baseline to follow-up (69.3 to 80.3, p < 0.001; 0.92 to 0.9, p = 0.009). Nearly one-third of participants (68/221, 31%) had mild or major depression at baseline. The proportion of participants with major depression decreased from baseline to follow-up (11.5% vs. 5%, p = 0.012). There was a moderate, significant positive correlation between depression and stigma scores (r = 0.41, p < 0.001). There were no differences found in TB stigma, self-rated health, QoL, or prevalence of mild/major depression between ACF and PCF participants. Conclusions We found a substantial, persistent, and clustered psychosocial impact among adults with TB diagnosed through both ACF and PCF strategies in Nepal. These findings suggest an urgent need to develop effective, evidence-based psychosocial support interventions with the potential to be integrated with existing ACF strategies and routine TB service activities.